2002
DOI: 10.1046/j.1439-0264.2002.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant Muscle Fibres in Pigs with Different Ryr1 Genotype

Abstract: This study examined the frequency, morphological and immunohistochemical characteristics of the giant fibres in the longissimus muscle of local Krsko polje pigs with different Ryr1 genotypes. Giant fibres were round-shaped and had significantly increased cross-sectional area compared with normal muscle fibres. Only fast-twitch glycolytic fibres were affected, usually showing enhanced succinate dehydrogenase activity. On the ultrastructural level, the dilation of the sarcoplasmic reticulum, swelling of mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
6
9
0
Order By: Relevance
“…Trapezius muscle is an abductor of the shoulder; its cervical portion pulls on the scapula in dorsocranial direction, its thoracic portion aids this movement by oscillating the dorsal part of the scapula in caudal direction. In agreement with the study of Fazarinc et al (2002), our study shows that the longissimus muscle is a typical white muscle in which fast-twitch glycolytic fibres dominate. It has been suggested that muscles with a high density of anaerobic fibres have a higher probability of being of poor eating quality, due to the more rapid accumulation of lactate and decline in pH (Van Laack et al 2001).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Trapezius muscle is an abductor of the shoulder; its cervical portion pulls on the scapula in dorsocranial direction, its thoracic portion aids this movement by oscillating the dorsal part of the scapula in caudal direction. In agreement with the study of Fazarinc et al (2002), our study shows that the longissimus muscle is a typical white muscle in which fast-twitch glycolytic fibres dominate. It has been suggested that muscles with a high density of anaerobic fibres have a higher probability of being of poor eating quality, due to the more rapid accumulation of lactate and decline in pH (Van Laack et al 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Muscle fibre hypertrophy occurs in animals in cases of congenital neuromuscular diseases and nutritional dystrophies, conditions that result in compensatory hypertrophies of some muscle fibres (Jubb et al 1985). In a study on local Kr‰ko polje pigs, Fazarinc et al (2002) reported the occurrence of giant fibres in porcine longissimus muscle is strongly correlated with the muscle pH, an indicator of early post-mortem glycolysis, leading to lactate formation in the tissue. Lactate is osmoticly active, binding intercellular water, which results in interstitial oedema and PSE condition of the muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giant fibres are characterized by swollen appearance and also show different histochemical staining pattern (Fazarinc et al 2002). However, apparently giant fibres do not occur in all pig breeds; they were not apparent in Black Sicilian pigs (Velotto et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…They are usually rounded in shape, larger than normal fibres and stain darker when coloured with haematoxylin-eosin. Giant fibres were first studied by Cassens et al (1969) and since then various authors have taken them into consideration, especially in swine where there seemed to be a connection between their presence and the PSE condition (Fazarinc et al, 2002;Severini and Loschi, 1997). This topic has recently also been considered in turkeys and chicken (Remignon et al, 2000;Mammoli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%